Nursing care for a family with a toddler in Lam Gawee Village, Darussalam Sub-District, Aceh Besar Regency - Nayumi Fadila Ratmoro; Neti Hartaty (Indonesian Journal of Health Science, 2026)
The family plays a crucial role in determining a child’s health status; however, optimizing care at the family level remains a challenge. During toddlerhood, rapid development is often accompanied by limited emotional regulation, which may trigger temper tantrums that can develop into behavioral problems if not addressed with appropriate parenting practices. Current child health issues indicate a high incidence of temper tantrums associated with parenting patterns, suboptimal exclusive breastfeeding practices, and incomplete basic immunization, all of which may affect overall child growth, development, and health status. This final scientific paper aimed to describe the implementation of family nursing care for a toddler using a family health tasks approach. The method used was a case study conducted in a family in Lam Gawee Village, Darussalam Sub-district, Aceh Besar, from December 17 to 26, 2025. Based on the assessment findings, the nursing diagnoses established were ineffective family coping related to temper tantrum behavior in toddlers, ineffective health maintenance behavior related to exclusive breastfeeding, and ineffective family self-health management related to immunization. Interventions focused on implementing the five family health tasks, including education on the concept and causes of temper tantrums and demonstration of management techniques during tantrum episodes. Evaluation results showed that family nursing care was effective in improving caregiver independence in managing temper tantrums, lactation management, and immunization adherence through the five-family health tasks approach. It is recommended that community nurses increase the frequency of home visits and provide anticipatory guidance to families on child-rearing practices, managing temper tantrums, and ensuring children’s health needs are met through exclusive breastfeeding and complete immunization.